Pemberdayaan Ibu Rumah Tangga Melalui Pembentukan Entrepreneur Mandiri di Kelurahan Johar Baru, Cempaka Putih: Empowering Housewives Through the Establishment of Independent Entrepreneurs in Johar Baru Village, Cempaka Putih - Harry Budiantoro; Imelda Sari; La Diadhan Hukama; Kanaya Lapae; Hestin Agus Tantri Ningsih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The purpose of this program is Community Service (PKM) which is a socialization program on how to create an entrepreneurial spirit to help housewives, young women, and the community increase their understanding of how to make, produce, and market patchwork waste decorations. in order to improve the family economy, is to carry out one of the functions of the Tridharma of Higher Education. Workshops and technical instructions in the manufacture of patchwork decorations are the methods used. 80% of the partners who attended were able to make decorative products from patchwork waste, according to the results of the pre and post tests that had been carried out. So with this training, it is hoped that housewives and young women in RW 03 Johar Baru Village will gain more knowledge about making simple businesses and being able to choose and sort patchwork materials and prepare tools.